Are all countries created the same? An asymmetric nexus between the COVID pandemic and G20 stock markets - Peterson Owusu Junior; Siva Kiran Guptha Kare (Cogent Economics & Finance, 2024)
The impact from COVID is dire to economies, and G20 countries are no exception irrespective of how developed their market are. This is due to how investors respond to bad and good news alike. Using daily data, for the G20 countries and data on COVID, we employ quantile regression (QR) and quantile-on-quantile regression (QQR) to explore the asymmetric nexus between COVID cases and G20 stock indices returns. Our results show that the pandemic fundamentally has a significant negative effect on all G20 stock returns with a heterogeneous nature across portions of the returns. Also, at varying quantiles of the distribution of stock, we highlight the fact that COVID pandemic has rather occasioned an asymmetric effect on G20 stock returns. Conversely, we notice positive link between the COVID and stock returns at the upper quantiles when the market started to bounce back from the crash. While the pandemic has largely slowed down, it is not completely swept out and the impacts may linger for a little long, hence investors are recommended to be more particular in the stock indices they wish to invest as they observe the erratic dynamics across the G20. The study is important to understand that for investors and policy-makers in the G20 countries, there are differences in how the COVID pandemic affected each country through their stock markets, and this is more complex than meets the eye. It should be noted that while concerted efforts are needed to address happenings like these, they should not be uniform. Investors need this information to spread their finances across the G20 markets to safeguard against losing it all.
Keywords: G20; 330; asymmetric impact; COVID; pandemic; quantile-on-quantile regression (QQR)